Modern approaches to the treatment of patients with chronic hepatitis B - S. F. Galimova; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. To present up-to-date references, that allows to choose the optimal mode of antiviral therapy for patient with chronic hepatitis B (CHB).Original positions. Chronic HBV-infection represents a major epidemiologic and economic problem all over the world. Liver cirrhosis (LC) and hepatocellular carcinoma (HCC) related to HBV infection are the causes for over 1 million deaths and 5–10% of transplantations of liver per year. The comprehension of the role of viral load in development of LC and HCC and introduction to the pharmaceutical market of new agents allow to improve guidelines on management of patients with chronic HBV-infection. The main criterion of efficacy of antiviral therapy (AVT) – the level of viral load. Monitoring of HBV DNA on the 12, 24, 48-th weeks of treatment enables to predict its efficacy and risk of development of resistance to nucleoside/nucleotides analogues. It is recommended to consider patients with CHB with viral load of over 2000 МЕ/ml (≈10000 copies/ml) and/ or elevation of alanineaminotransferase (ALT) activity, with signs of moderate to severe inflammatory-necrotic changes and/or liver fibrosis as candidates for AVT. Patients with LC are considered as candidates for AVT even at normal ALT levels irrespective of level of viral load. For decompensated LC patients nucleoside/ nucleotides analogues are the drugs of choice. New analogues nucleoside/nucleotides (telbivudine, entecavir, tenofovir) have direct antiviral action and good tolerability at long application.Conclusion. Modern international references on management of patients with HBV-infection allows to increase efficacy of treatment by of rational application of antiviral agents, to improve survival rate, to reduce mortality and risk of LC and HCC development, to optimize treatment cost.